Hepatic metallothionein concentrations in the golden grey mullet (Liza aurata) - Relationship with environmental metal concentrations in a metal-contaminated coastal system in Portugal - Oliveira, M.
This field survey was designed to assess the environmental metal contamination status of Ria de Aveiro (Portugal). To achieve that goal, the concentrations of Cd, Hg, Cu and Zn in the sediments and water were assessed and Liza aurata hepatic metallothionein (MT) determined. The relationships between MT and environmental metal concentrations and hydrological factors were examined. Results revealed a wide distribution of metals both in water and sediments throughout the lagoon, mainly at Rio Novo do Principe (RIO) and Laranjo (LAR), at concentrations that may affect biota. MT concentrations were higher at the sites with high metal content (RIO and LAR). A significant positive correlation was found between MT and Cd in the sediments as well as with MT and Hg and Cu in the water. Moreover, a negative correlation between MT and salinity was found. Thus, the current data support MT use as a biomarker of metal exposure emphasizing the importance of hydrological parameters in its concentrations. Results suggest the continued monitoring of this lagoon system.